Prognostic impact of the updated 2018 HFA‐ESC definition of advanced heart failure: results from the HELP‐HF registry. (31st May 2022) - Pagnesi, Matteo; Lombardi, Carlo Mario; Chiarito, Mauro; Stolfo, Davide; Baldetti, Luca; Loiacono, Ferdinando; Tedino, Chiara; Arrigoni, Luca; Ghiraldin, Daniele; Tomasoni, Daniela; Inciardi, Riccardo Maria; Maccallini, Marta; et al.
Abstract : Aims: The Heart Failure Association of the European Society of Cardiology (HFA‐ESC) proposed a definition of advanced heart failure (HF) that has not been validated, yet. We assessed its prognostic impact in a consecutive series of patients with high‐risk HF. Methods and results: The HELP‐HF registry enrolled consecutive patients with HF and at least one high‐risk 'I NEED HELP' marker, evaluated at four Italian centres between 1 st January 2020 and 30 th November 2021. Patients meeting the HFA‐ESC advanced HF definition were compared to patients not meeting this definition. The primary endpoint was the composite of all‐cause mortality or first HF hospitalization. Out of 4753 patients with HF screened, 1149 (24.3%) patients with at least one high‐risk 'I NEED HELP' marker were included (mean age 75.1 ± 11.5 years, 67.3% male, median left ventricular ejection fraction [LVEF] 35% [interquartile range 25%–50%]). Among them, 193 (16.8%) patients met the HFA‐ESC advanced HF definition. As compared to others, these patients were younger, had lower LVEF, higher natriuretic peptides and a worse clinical profile. The 1‐year rate of the primary endpoint was 69.3% in patients with advanced HF according to the HFA‐ESC definition versus 41.8% in the others (hazard ratio [HR] 2.23, 95% confidence interval [CI] 1.82–2.74, p < 0.001). The prognostic impact of the HFA‐ESC advanced HF definition was confirmed after multivariable adjustment for relevant covariates (adjusted HR 1.98, 95% CI 1.57–2.50, p < 0.001). Conclusions: The HFA‐ESC advanced HF definition had a strong prognostic impact in a contemporary, real‐world, multicentre high‐risk cohort of patients with HF. Abstract : Distribution and prognostic impact of the 2018 Heart Failure Association of the European Society of Cardiology (HFA‐ESC) advanced heart failure (HF) criteria in the HELP‐HF (Assessment of the I Need Help markers in Heart Failure) registry. Consecutive patients with HF who were hospitalized or evaluated as outpatients between January 2020 and November 2021 at four Italian high‐volume centres and had at least one 'I Need Help' high‐risk marker ( n = 1149) were included in the HELP‐HF registry (upper left panel). Among the included patients, 240 (20.9%) had no criteria for advanced HF according to the updated HFA‐ESC definition, whereas 193 (16.8%) had all four criteria and therefore met the HFA‐ESC definition of advanced HF (lower left panel). A progressively higher risk of the primary composite endpoint of all‐cause mortality or first HF hospitalization at 1 year was observed with an increasing number of HFA‐ESC advanced HF criteria (right panel), and patients meeting the HFA‐ESC definition of advanced HF (i.e. with all four criteria) had the highest risk of adverse outcomes (1‐year rate of the primary composite endpoint 69.3%; adjusted hazard ratio [HR] vs. patients with no criteria 2.40, 95% confidence interval [CI] 1.74–3.30). KM, Kaplan–Meier.